ANALISIS PENGARUH LOAN TO DEPOSIT RATIO TERHADAP PROFITABILITAS DENGAN NET INTEREST MARGIN SEBAGAI VARIABEL INTERVENING PADA BANK UMUM KONVENSIONAL PERSERO YANG TERDAFTAR DI OJK - Wakid, Royhan Tofail; Sari, Lita Permata; Subaida, Ida (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Bank is one of the institutions of stability of the financial system and banking system of a country that has prospects in the future in all economic conditions. State-owned conventional banks registered with the Otoritas Jasa Keuangan (OJK) have been supervised with integrity so that they are able to provide trust for users of financial services. The purpose of this study is to analyze the effect of the Loan to Deposit Ratio on Profitability at Persero conventional banks at OJK through Net Interest Margin. This research uses descriptive and quantitative methods. The population of this study are conventional banks registered with the Otoritas Jasa Keuangan (OJK). The sampling technique was determined by purposive sampling method. Data analysis and testing using Structural Equation Model – Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, indicate that the Loan to Deposit Ratio has a significant negative effect on Net Interest Margin, Loan to Deposit Ratio has no significant effect on Profitability, and Net Interest Margin has a significant effect on Profitability. The results of the indirect effect hypothesis test show that the Loan to Deposit Ratio variable on Profitability through Net Interest Margin has a significant negative effect.